Factors Influencing Binge-watching Behaviour and its Impact on Loneliness among Undergraduate Medical Students: A Cross-sectional Study from Chengalpattu District, Tamil Nadu, India - R Suba Shree; P Kaveri; Roshni Mary Peter; VV Anantharaman; M Logaraj (Journal of Clinical and Diagnostic Research)
Introduction: Binge-watching, a common behaviour among youth, is especially prevalent among medical students due to academic pressures and the accessibility of streaming services. This behaviour may lead to potential mental and physical health impacts. Aim: To assess the prevalence of binge-watching and identify associated risk factors among undergraduate medical students. Materials and Methods: A cross-sectional study was conducted among MBBS students in Chengalpattu, Tamil Nadu, India using multistage sampling. A total of 400 students were selected through simple random sampling. Socio-demographic details, including age, gender, family type, residence, year of study and risk factors for binge-watching (such as sleep duration, participation in recreational activities, Over-The-Top (OTT) platform subscription status, the number of OTT platforms subscribed to, frequency of binge-watching, devices used for binge-watching and consumption of snacks or junk food during binge-watching), were gathered using a pretested semistructured questionnaire. The University of California, Los Angeles (UCLA) Loneliness Scale and the Binge-watching Addiction Questionnaire assessed loneliness and binge-watching behaviour. Statistical analysis included mean and standard deviation, independent t-tests for continuous variables, Chi-square tests, univariate regression for categorical variables, and binary logistic regression for significant variables (p-value<0.05) to control for confounders. Results: The participants had a mean age of 20.71±2.04 years, with the majority being females (58.6%) and from nuclear families (86.1%). Most students (84.4%) had subscriptions to OTT platforms, with 50.8% binge-watching more than twice a week. The prevalence of binge-watching was 64% (381 participants). The overall mean binge-watching score was 33.14±13.012. Mild binge-watching was observed in 172 students (70.5%), moderate binge-watching in 53 students (21.7%), and problematic binge-watching in 19 students (7.8%). The overall mean loneliness score was 44.44±9.39. Univariate analysis identified significant associations between problematic binge-watching and being a hosteller, lack of recreational activities, OTT platform subscription and consumption of snacks or junk food. Binary logistic regression revealed significant associations between problematic binge-watching and factors such as the absence of recreational activities (AOR=2.298, p-value=0.012) and consuming snacks (AOR=2.518, p-value=0.006). Higher loneliness scores were significantly associated with problematic binge-watching (46.67±8.85) compared to mild binge-watching (43.51±9.47) (p-value=0.016). Conclusion: The study revealed a high prevalence of binge-watching among medical students, which was linked to loneliness and a lack of recreational activities. This emphasises the need for awareness and interventions to promote balanced media consumption.